Diketopyrrolopyrroles disubstituted with alkylated thiophenes: effect of the donor unit size and solubilizing substituents on their redox, photo- and electroluminescence properties1. Issue 73 (9th August 2015) - Wiosna-Salyga, Gabriela; Gora, Monika; Zagorska, Malgorzata; Toman, Petr; Luszczynska, Beata; Pfleger, Jiri; Glowacki, Ireneusz; Ulanski, Jacek; Mieczkowski, Jozef; Pron, Adam
<x xml:space="preserve">Abstract</x> Diketopyrrolopyrroles disubstituted with thiophene derivatives can be used as effective luminophores in guest/host type light emitting diodes.